Proteína degradável no rúmen e frequência de suplementação para recria de novilhos em pastejo - De Figueiredo Assad, Leonardo Vaz; Zervoudakis, Joanis Tilemahos; Da Silva Cabral, Luciano; Hatamoto-Zervoudakis, Luciana Keiko; Da Silva-Marques, Renata Pereira; Koscheck, Jefferson Fabiano Werner [UNESP]; Toledo, Éder Rodrigues; Micheletti, Marcus Vinicius (Universidade Estadual de Londrina, 2015)
It was aimed to evaluate the effect of the rumen degradable protein (RDP) and supplementation frequency on the consumption and digestibility of the nutrients, concentration of amoniacal nitrogen (N-NH3), ruminal pH and nitrogen compounds excreted in the urine (NUR) and serum (NS) in bovine in pasture of Brachiaria brizantha cv. Marandu during the rainy/dry transition period. Five crossbred steers, castrated, with average body weight of 350 kg, cannulated in the rumen, were used. The experiment used in Latin square design 5 × 5, with duration of 21 days each experimental period. The treatments were: SAL - mineral mix supplied ad libitum (Controls); daily RDP: supplement formulated to meet the requirements RDP, with daily supply; frequency RDP: supplement formulated to meet the requirements RDP, supplied three times on week (Mondays, Wednesdays and Fridays); RDP+: supplement formulated with increment of 10% of the requirements of RDP supplied 3X; RDP-: supplement formulated with less 10% of the requirements of RDP supplied 3X. There was statistical difference for dry matter intake (DMI), forage (CFO) and neutral detergent fiber (NDF) and apparent digestibility of DM and NDF with treatment effect (p <0.05), after being checked by statistically significant contrast analysis (p <0.05) between supplements (Ps vs. RDP daily). Providing multiple supplementation increased or reduced by 10% in RDP requirements of animals and controlled add-frequency did not affect (P> 0.05) DMI and apparent digestibility of DM, CP and NDF. The ruminal pH was different between the frequency RDP supplements vs. RDP-time 4 hours on day no supplementation. The ruminal ammonia concentration of the supplemented animals showed a difference between the RDP daily supplements vs. RDP frequency; RDP frequency vs. RDP +; RDP frequency vs. PDR-. The nitrogen serum concentration is larger (P < 0.10) in animals consuming multiple supplements with increment of 10% of the requirements of RDP.
Degradable protein in rumen and frequency of supplementation for it recreates of bovine in pasture
Keywords: Ammonia; Consumption; Digestibility; Multiple supplements